A mouse model of endometriosis mimicking the natural spread of invasive endometrium - Wilson, Mike R; Holladay, Jeanne; Chandler, Ronald L (Human reproduction (Oxford), 2020)
Is it possible to establish a genetically engineered mouse model (GEMM) of endometriosis that mimics the natural spread of invasive endometrium? Endometriosis occurs in an ARID1A (AT-rich interactive domain-containing protein 1A) and PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha) mutant GEMM of endometrial dysfunction following salpingectomy. Although mouse models of endometriosis have long been established, most models rely on intraperitoneal injection of uterine fragments, steroid hormone treatments or the use of immune-compromised mice. Mice harboring the lactotransferrin-Cre (LtfCre0/+), Arid1afl, (Gt)R26Pik3ca*H1047R and (Gt)R26mTmG alleles were subject to unilateral salpingectomies at 6 weeks of age. Control (n = 9), LtfCre0/+; (Gt)R26Pik3ca*H1047R; Arid1afl/+ (n = 8) and LtfCre0/+; (Gt)R26Pik3ca*H1047R; Arid1afl/fl (n = 9) were used for the study. The (Gt)R26mTmG allele was used for the purpose of fluorescent lineage tracing of endometrial epithelium. LtfCre0/+; (Gt)R26mTmG (n = 3) and LtfCre0/+; (Gt)R26Pik3ca*H1047R/mTmG; Arid1afl/fl (n = 4) were used for this purpose. Mice were followed until the endpoint of vaginal bleeding at an average time of 17 weeks of age. At 6 weeks of age, mice were subjected to salpingectomy surgery. Mice were followed until the time point of vaginal bleeding (average 17 weeks), or aged for 1 year in the case of control mice. At time of sacrifice, endometriotic lesions, ovaries and uterus were collected for the purpose of histochemical and immunohistochemical analyses. Samples were analyzed for markers of the endometriotic tissue and other relevant biomarkers. Following salpingectomy, LtfCre0/+; (Gt)R26Pik3ca*H1047R/mTmG; Arid1afl/fl mice developed endometriotic lesions, including lesions on the ovary, omentum and abdominal wall. Epithelial glands within lesions were negative for ARID1A and positive for phospho-S6 staining, indicating ARID1A-PIK3CA co-mutation status, and expressed EGFP (enhanced green fluorescent protein), indicating endometrial origins. N/A. LtfCre0/+; (Gt)R26Pik3ca*H1047R; Arid1afl/fl mice develop vaginal bleeding as a result of endometrial dysfunction at an average age of 17 weeks and must be sacrificed. Furthermore, while this model mimics the natural spread of endometriotic tissue directly from the uterus to the peritoneum, the data presented do not reject current hypotheses on endometriosis pathogenesis. The idea that endometriosis is the result of abnormal endometrial tissue colonizing the peritoneum via retrograde menstruation has gained widespread support over the past century. However, most models of endometriosis take for granted this possibility, relying on the surgical removal of bulk uterine tissue and subsequent transplantation into the peritoneum. Growing evidence suggests that somatic mutations in ARID1A and PIK3CA are present in the endometrial epithelium. The establishment of a GEMM which mimics the natural spread of endometrium and subsequent lesion formation supports the hypothesis that endometriosis is derived from mutant endometrial epithelium with invasive properties. This research was supported by the American Cancer Society PF-17-163-02-DDC (M.R.W.), the Mary Kay Foundation 026-16 (R.L.C.) and the Ovarian Cancer Research Fund Alliance 457446 (R.L.C.). The authors declare no competing interests.